2020
DOI: 10.1093/cdn/nzaa045_063
|View full text |Cite
|
Sign up to set email alerts
|

Cranberry-Derived Proanthocyanidin and Its Gut Microbial Metabolites Affect the Intestinal miRNome in a Distinct Manner In Vitro

Abstract: Objectives Polyphenols are emerging as novel prebiotic compounds. Cranberries are a rich source of polyphenols, such as proanthocyanidin (PAC), which has known benefits including anti-cancer properties. In the colon, PACs are catabolized by the gut microbiota into 3,4-dihydroxyphenylacetic acid (DHPAA) and 3-(4-hydroxyphenyl) propionic acid (HPPA), which may mediate prebiotic effects. Mechanisms are unknown but may involve host microRNA (miRNA). The objective of this study was to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recent studies have shown that cranberry polyphenols gut metabolites 3,4-dihydroxyphenylacetic acid and 3-(4-hydroxyphenyl) propionic acid may mediate prebiotic effects by modulating small noncoding endogenous microRNA (miRNA) profiles in colonic cells (Lofft, Taibi, & Comelli, 2020). However, extrapolating these in vitro results to explain cranberry effects on human health is difficult and warrant further preclinical studies, particularly pharmacokinetics, and metabolism studies of these metabolites in vivo.…”
Section: Gut Microbial Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that cranberry polyphenols gut metabolites 3,4-dihydroxyphenylacetic acid and 3-(4-hydroxyphenyl) propionic acid may mediate prebiotic effects by modulating small noncoding endogenous microRNA (miRNA) profiles in colonic cells (Lofft, Taibi, & Comelli, 2020). However, extrapolating these in vitro results to explain cranberry effects on human health is difficult and warrant further preclinical studies, particularly pharmacokinetics, and metabolism studies of these metabolites in vivo.…”
Section: Gut Microbial Metabolitesmentioning
confidence: 99%
“…Similarly, probiotic metabolites of cranberry polyphenols by Lactobacillus rhamnosus, such as 4-hydroxyphenylacetic acid, have cell growth inhibitory effects against hepatocellular carcinoma HepG2 cells in vitro (Rupasinghe, Parmar, & Neir, 2019). As for other polyphenol metabolites, structural changes during metabolic transformation of CPs may lead to increased or decreased activities (van Duynhoven et al, 2011).Recent studies have shown that cranberry polyphenols gut metabolites 3,4-dihydroxyphenylacetic acid and 3-(4-hydroxyphenyl) propionic acid may mediate prebiotic effects by modulating small noncoding endogenous microRNA (miRNA) profiles in colonic cells(Lofft, Taibi, & Comelli, 2020). However, extrapolating these in vitro results to explain cranberry effects on human health is difficult and warrant further preclinical studies, particularly pharmacokinetics, and metabolism studies of these metabolites in vivo.In recent years, it is becoming increasingly clear that the composition of gut microbiota is highly individualized and associated with the host health.…”
mentioning
confidence: 99%
“…Another possible factor is a mutation on TP53, the gene encoding P53, which activates HAMP transcription (Hussain et al 2007 , Shen et al 2014 ). Also, there may be an elevation of matriptase-2 expression, which acts as a negative regulator for hepcidin expression (Lofft et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%